PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA AKUNTAN PEMERINTAH (Studi Empiris Pada Perwakilan BPKP Provinsi Riau) - Raf, Andres Gunaldo; Wiguna, Meilda; ', Desmiyawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Government accountants are professional accountants who work in government agencies that their main duty conduct an examination of the financial liability that is presented by organizational units within the government or financial liability to the government. One is an accountant who works in the Financial and Development Supervisory Agency.This study aims to determine the Effects of Leadership Style, Organizational Culture, Work Motivation and Work Environment toward Performance of Government Accountants In BPKP Representative Riau Province . Respondents in this study are numbered 110 people. The type of data used is the data subject and the data in the form of a data source with the primary data source using the questionnaire method of data collection. The method of data analysis used in this study is a multiple linear regression ( multiple regression ) with the help of SPSS software version 19.0 . The results of this study showed, partially variable Leadership Style, Organizational Culture, Work Motivation and Work Environment significantly has affect to the performance of government accountants. While the coefficient of determination of independently showed all variables used in this study provide a contribution of 43,4 % to the dependent variable. While the remaining 56,6 % describe other independent variables that are not observed in this study.Keywords : leadership styles, organizational culture, work motivation, work environment, the performance of government accountants.